Foreign direct investment, current and capital accounts: a cointegration analysis - Kesaobaka, M.; Daw, O. D.; Mongale, I. P. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
The current account, capital and financial accounts make up a country’s balance of payments. These accounts tell a story about the state of an economy, its economic outlook and its strategies for attaining its foreseen goals. By means of cointegration and VECM approach, this study examines the impact of current and capital accounts on foreign direct investment in South Africa. The cointegration test results reveal the presence of a long run economic relationship amongst the variables implying that they share a common linear. Furthermore, foreign direct investment has a significant and positive relationship with current account and capital account in the short-run. GDP, which was, introduced as a control variable in the system showed an insignificant and negative relationship with foreign direct investment. Apart from contribution to the literature, the findings of this study are valuable for international organisations and the African governments in terms of future policies. The study recommends that the government should continue with the strategy of attracting more foreign investors into South Africa, because the money help boost domestic productivity and thus have a potential to expand the economy.
Journal article
Keywords: Foreign Direct Investment; Current account; Capital account; South Africa; Investments, Foreign; Accounts current; Balance of payments -- South Africa